TIME AND MOTION STUDY PEKERJAAN PENYANGGAAN PADA LOKASI PRODUKSI TAMBANG CIGUHA UTAMA PT. ANTAM (PERSERO) TBK UBPE PONGKOR - Deddy H. Elias; Indra Birawaputra (INTAN Jurnal Penelitian Tambang, 2018)
Time and motion study is a method of time measurement process, from which time wasting in ground support task that involve human interventions, could be reduced. This method was utilised to figure out the efficiency resulted by buffering tasks, as well as to analyse the work cycle produced by supporting crews of Mega Mustika Utama in PT. Antam Tbk. UBPE Pongkor. The results revealed that the efficiency in workhours of ground support task included survey of location, job cards, and time for meals. The daily work cycle begun from change self protection tools at the beginning of the shift to the replacement of self protection tools at the end of the shift. The results also highlighted that the highest work efficiency of buffering tasks was 84.10%, and the lowest work efficiency was 25.83%